EVALUATION OF FINTECH REGULATORY LIMITATIONS IN GCC COUNTRIES - Yousef, Talal (2019)
The implementation of Fintech in GCC countries has grown over time. The region through mentorship of global technological changes has found itself on the verge of increasing changes in informational and technological infrastructure. However, the region still faces challenges in realizing financial technology transformation. The study emphasizes on the regulatory impact on Fintech development in GCC. Fintech is being driven by changing consumer demands and preferences in the region. the larger part of the GCC market is still loyal to traditional Islamic banking, which contradicts the uprising regional and global market shift that drifting the industry in the GCC members to acknowledge the need to implement proper Fintech regulations that can promote its development. The study uses qualitative secondary data method to analyze the introduction and transformation of Fintech contrary to regulatory limitations and loyalty to the traditional financial system and the assertive regulations. Saudi Arabia, Kuwait, UAE, Oman, Qatar, and Bahrain exhibit the significant role of Fintech in their development. The nations have low entry barriers and insubordination through their traditional practices and regulations for new financial technologies. The GCC laws restrict the entry of new Fintech firms by preserving certain operations to the Islamic institution but while also prioritizing the Islamic institutions for the implementation of the modern financial models. The Fintech innovations target financial services such as payments, deposits, credits, insurances, wealth management, and raising capital. Thus, the focus of the study is on regulatory limitations to Fintech development in GCC that undermines the potentiality of the industry.